2012
DOI: 10.1111/j.1751-3928.2012.00185.x
|View full text |Cite
|
Sign up to set email alerts
|

The Arinem Te‐Bearing Gold‐Silver‐Base Metal Deposit, West Java, Indonesia

Abstract: The vein system in the Arinem area is a gold-silver-base metal deposit of Late Miocene (8.8-9.4 Ma) age located in the southwestern part of Java Island, Indonesia. The mineralization in the area is represented by the Arinem vein with a total length of about 5900 m, with a vertical extent up to 575 m, with other associated veins such as Bantarhuni and Halimun. The Arinem vein is hosted by andesitic tuff, breccia, and lava of the OligoceneMiddle Miocene Jampang Formation (23-11.6 Ma) and overlain unconformably b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 14 publications
0
18
0
1
Order By: Relevance
“…Investigations of the fluid inclusions in the Arinem samples (Yuningsih et al, 2012) revealed that the main-stage quartz vein was deposited at the average homogenization temperature (T h ) of 194-267°C, with a general decrease in temperature with decreasing depth and advancing paragenetic time (Table 1). However, one quartz sample belonging to stage IA shows evidence of boiling; this sample contains both gas-rich and liquid-rich inclusions along the same growth band.…”
Section: Fluid Inclusionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Investigations of the fluid inclusions in the Arinem samples (Yuningsih et al, 2012) revealed that the main-stage quartz vein was deposited at the average homogenization temperature (T h ) of 194-267°C, with a general decrease in temperature with decreasing depth and advancing paragenetic time (Table 1). However, one quartz sample belonging to stage IA shows evidence of boiling; this sample contains both gas-rich and liquid-rich inclusions along the same growth band.…”
Section: Fluid Inclusionsmentioning
confidence: 99%
“…It should be noted that not all stages of mineralization can be recognized in every part of the Arinem vein. A general description of these mineralization stages was made by Yuningsih et al (2012) and for the purposes of further interpretation, detailed mineral paragenetic sequences are presented below. …”
Section: Vein Mineralizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of ore mineralogy and geochemistry were carried out within the epithermal ore deposits of western Java by previous authors such as Pongkor (Basuki et al, 1994;Marcoux and Milesi, 1994;Sukarna et al, 1994;Milesi et al, 1999;Sukarna, 1999;Warmada et al, 2003;Syafrizal et al, 2005;Syafrizal et al, 2007;Warmada et al, 2007), Cikidang (Rosana and Matsueda, 2002), Cibaliung (Sudana and Santosa, 1992;Marcoux and Milesi, 1994;Marjoribanks, 2000;Angeles et al, 2002;Harijoko et al, 2004;Harijoko et al, 2007), Cisungsang (Rosana et al, 2006), Cirotan , Arinem (Yuningsih et al, 2012), and Cineam (Widi and Matsueda, 1998).…”
Section: Introductionmentioning
confidence: 99%